2013
DOI: 10.3144/expresspolymlett.2013.84
|View full text |Cite
|
Sign up to set email alerts
|

Processing – morphology – property relationships of polyamide 6/polyethylene blend–clay nanocomposites

Abstract: Abstract. In this work, we studied the effect of the method of preparation and of reprocessing on the morphology and, consequently, on the physical properties of polyamide 6 (PA6)/ high density polyethylene (HDPE)-clay nanocomposite blends in the presence of different compatibilizers. In particular, the nanocomposites were obtained by melt mixing using a corotating twin screw extruder (E1). The blends thus obtained were re-extruded (E2) under the same operating conditions. Moreover, blends with the same final … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…The supplementary stresses induced on the composite by multiple reprocessing allow yet a further dispersion of the MMT filler with consequently a higher intercalation level. This enhancement in interlayer distance by multiple processing has also been reported in other polymeric matrices by other authors; for example in a polyamide-polyethylene blend [32], poly (acrylonitrile-butadiene-styrene) [20] and polyamide [16].…”
Section: Discussionmentioning
confidence: 54%
“…The supplementary stresses induced on the composite by multiple reprocessing allow yet a further dispersion of the MMT filler with consequently a higher intercalation level. This enhancement in interlayer distance by multiple processing has also been reported in other polymeric matrices by other authors; for example in a polyamide-polyethylene blend [32], poly (acrylonitrile-butadiene-styrene) [20] and polyamide [16].…”
Section: Discussionmentioning
confidence: 54%
“…4(a). 26,27 At the same time, from Fig. 7(b) we can see that the varying trends in tensile strength of PET/ PA6 (30/70) nanocomposites are complicated.…”
Section: Mechanical Property Of the Nanocompositesmentioning
confidence: 91%
“…These concerns are related to possible degradation occurring during processing and reprocessing, particularly when multiple reprocessing cycles are performed [76]. Scaffaro et al [77] found that re-extrusion slightly improves the morphology of PA 6/PE blend-clay nanocomposites most likely due to the supplementary stresses induced on the blend in the second processing step, allowing further dispersion of the nanofiller with a consequently higher intercalation level.…”
Section: 2mentioning
confidence: 99%